Pengaruh Modifikasi Permainan Bola Besar Sepak Bola terhadap Motivasi Siswa dalam Pembelajaran PJOK - Muhammad Iqbal Maulana; Afifan Yulfadinata (SPRINTER: Jurnal Ilmu Olahraga, 2026)
The purpose of this study was to investigate how students' learning motivation in physical education (PJOK) was affected by changing big ball games using a Small-Sided Games (SSG) strategy. The study used a pretest–posttest control group design and a quantitative experimental method. 59 seventh-grade students participated in the study, which was carried out at SMP Negeri 59 Surabaya. There were 30 students in the experimental group and 29 in the control group. While the control group was instructed using traditional teaching techniques, the experimental group was taught football through modified small-sided games. A motivation questionnaire modified from other studies was used to gauge students' motivation for studying. Descriptive statistics, Levene's homogeneity test, Shapiro-Wilk normality test, independent samples t-test, and paired samples t-test were all used in the data analysis. Following the use of the SSG strategy, students in the experimental group demonstrated a considerable increase in learning desire; paired sample analysis revealed a statistically significant difference (p < 0.001). Additionally, posttest results showed that learning motivation differed significantly between the experimental and control groups (p < 0.05). These results suggest that small-sided games are a useful teaching method for raising students' motivation to study in physical education. In order to facilitate meaningful learning experiences in PJOK, the study highlights the significance of student-centered and game-based learning methodologies. References, tables, graphs, and a motivation questionnaire are used as supporting materials in this article.